Incidence, predictors, and survival of pulmonary hypertension determined by echocardiography in Thai patients with early systemic sclerosis (SSc): inception cohort study - Suparaporn Wangkaew (2020)
© 2020, International League of Associations for Rheumatology (ILAR). Objectives: We investigated the incidence, predictors, and survival of pulmonary hypertension (PH) determined by Doppler echocardiography in Thai patients with early SSc (systemic sclerosis), in which the majority were diffuse cutaneous SSc (DcSSc) with anti-topoisomerase I-positive. Methods: We used an inception cohort study of patients with early SSc seen at the Rheumatology Clinic, Maharaj Nakorn Chiang Mai Hospital. All patients were assessed for clinical data and underwent Doppler echocardiography at the study entry and then annually. Results: A total of 133 patients (81 female, 106 DcSSc, 103 anti-topoisomerase I-positive) with a mean disease duration of 11.9 months were recruited. During the mean observational period of 4.2 years, 14 patients developed PH concurrent with ILD and 6 with left heart disease. The incidence rate for the development of PH was 3.95 per 100 person years. The multivariate Cox regression analysis indicated higher NYHA class (HR 6.90, 95% CI 2.28–20.94, p = 0.001), telangiectasia (HR 4.18, 95% CI 1.25–13.92, p = 0.020), and enlarged LA diameter (HR 1.16, 95% CI 1.05–1.28, p = 0.005) as predictors of PH. Raynaud’s phenomenon (HR 0.22, 95% CI 0.06–0.84, p = 0.026) and high oxygen saturation (HR 0.80, 95% CI 0.65–0.99, p = 0.047) were protective factors. The survival rate after PH diagnosis at 1, 3, and 5 years were 88.9%, 82.3%, and 48.0%, respectively. Conclusions: In this study cohort, the majority had early DcSSc, the incidence of PH was modest, and all cases developed concomitantly with ILD or left heart disease, resulting in poor survival. The presence of higher NYHA class, telangiectasia, and enlarged LA diameter was predictors of secondary PH. Further study regarding the treatment strategies for PH associated with ILD and left heart disease in SSc is needed.• In this cohort of early SSc in which the main subtype was DcSSc, the incidence of PH was modest and all PH was secondary PH associated with ILD and left heart disease, resulting in poor survival.• The presence of higher NYHA functional class, telangiectasia, and enlarged LA diameter was baseline predictors of developing secondary PH.• Effective treatment strategies for secondary PH due to ILD and cardiac involvement in SSc patients are urgently needed.